Shaking Table Test Investigation on Seismic Performance of Joint Model of Immersed Tunnel - Xueming Zhang; Linlin Song; Hongjuan Chen; Shicai Chen; Zhinan Hu; Yong Li (Shock and Vibration)
Critical for the seismic safety of immersed tunnels is the magnitude of deformation and force developing in the segment joints. To investigate the seismic performance of segment joint in immersed tunnel, this paper presents a series of shaking table arrays tests that were performed on a microconcrete tunnel model embedded in the soil. The tests take account of the uniform and wave passage effect in different apparent wave velocity of longitudinal seismic excitation. The result showed that the wave passage effect had a great impact on axial force, bending moment and deformation of joints. The comparison showed that structural response under nonuniform earthquake excitation is larger than that under uniform excitation. The simplified model was established in ABAQUS for numerical analysis. The soil around the tunnel was simplified as spring-damper, the tunnel was simplified as beam element, and the joint was simulated by nonlinear spring. The numerical simulation results were in good agreement with the experimental data. In addition, the model was analyzed by changing input apparent wave velocity, joint stiffness and joint number. The results showed that the deformation of joints was smaller and the deformation of flexible joints was greater under high apparent wave velocity.